دلالـــــة العنــــــوان فــــي المصادر اللّغويّة والأدبيّة العربيّة القديمة - بوبكر مسعي، بوبكر, التجاني مسعي، محمد (University of Eloued, 2019)
This research attempt to identify in deeply the Arab heritage in general by studying the titles of some linguistic and literary sources. It has been divided into two chapters: - Chapter I: theoretic entitled «the definition of concepts», when we identified "semantics and semantics withe title and finally sources" We have dealt with these aspects in detail not boring and accuracy given that these issues are the mainstays of our research, we must pay much attention.. - Chapter II: It was a pure application and entitled «The significance of the title in the ancient Arab sources» We divided into three sections: • Linguistic Sources: We touched on the «MOKTADAB» by by El MOUBARED, «MEFTAH El-AOULOUM» by SAKAKI, «MOUGHANI EL-BiB AAN QUOTEB El-ARAB» by f IBN HICHAM, «El-MOZHER in the sciences and types of language» by SUYUTI . • Dictionaries: We analyzed the «El Ain» by Khalil bin Ahmed, «LISSANE El-ARAB» by Ibn Manzoor, «El QUAMOUSS El-MOUHIT » by FAIROUZ ABAD, «TAGJ El AROUS MEN DJAOUHAR El-QUAMOUS» ZUBAIDI. • Literary sources: In which we touched on «El-MEFDALIAT» by El MOUFADEL -ADABI, «AOUYOUN El AKHBAR» by IBN QUOTAIBA, «El-KAMEL FI ELLOUGHA WEL-ADAB » EL-MOUBARED, «EL-IKD -ELFARID» IBN ABD RABOU EL ANDALOUSSI, «SUBH EL-AACCHA FI SINAET AL INCHA» by EL-QUALQUACHAVDI. We listed these sources in chronological order, and we followed the historical order. هذا البحث محاولة للتّعرف على التراث العربي عامّة و التّعمّق فيه من خلال دراسة عناوين بعض المصادر اللغويّة والأدبية وقد تمّ تقسيمه إلى فصلين : - الفصل الأول : وكان نظريا وعنوانه « تحديد المفاهيم » ، حدّدنا فيه "الدّلالة وعلم الدلالة و العنوان وأخيرا المصادر" وقد تناولنا هذه الجوانب بشيء من التفصيل غير الممل إلى جانب توخي الدّقة باعتبار أنّ تلك المسائل هي دعائم أساسيّة يقوم عليه بحثنا يجب أن نوليها الكثير من الاهتمام . - الفصل الثاني : وكان تطبيقيّا خالصا وعنوانه « دلالة العنوان في المصادر العربيّة القديمة» قسمناه إلى ثلاثة أقسام هي : • المصادر اللغوية: وتطرّقنا فيها إلى « المقتضب » للمبرد ، « مفتاح العلوم » للسّكاكي ، « مغني اللبيب عن كتب الأعاريب » لابن هشام، « المزهر في علوم اللغة وأنواعها» للسيوطي . • المعاجم: وحلّلنا فيه « العين » للخليل بن أحمد ، « لسان العرب» لابن منظور، « القاموس المحيط » للفيروزأبادي ، « تاج العروس من جواهر القاموس» للزبيدي . • المصادر الأدبيّة: وفيه تطرّقنا إلى « المفضليات » للمفضل الضّبي ، « عيون الأخبار» لابن قتيبة ، « الكامل في اللغة والأدب » للمبرد ،« العقد الفريد » لابن عبد ربه الأندلسي ، « صبح الأعشى في صناعة الإنشاء » للقلقشندي . وقد أوردنا هذه المصادر حسب ترتيبها الزمني، فاتّبعنا الترتيب التاريخي .
Keywords: Significance of the title - linguistic sources - ancient - Arabic; دلالـــــة العنــــــوان- المصادر اللّغويّة - القديمة - العربيّة